Diegetic presence in cinematic virtual reality - Chung, Justine (Tufts University. Tisch Library., 2018)
A unique feature of cinematic virtual reality (CVR) as a medium is its attempt to produce in its viewer a sense of diegetic presence: authors of CVR use techniques to promote in the viewer a feeling that she is within the story-world represented by CVR, as mediated through the head-mounted display. This poster represents the findings from my preliminary research in the summer of 2018. I argue that CVR authors' priority of presence preservation is heavily shaping the aesthetics of this medium. I then discuss modes of diegetic presence, and the particular experiences these modes afford. This work will be continued in my thesis research, beginning in Spring 2019. Submitted in partial fulfillment of the grant requirement of the Tufts Summer Scholars Program.